Integrating network pharmacology and transcriptomics to reveal the therapeutic effect of Long Mu Ning Xin Decoction on attention-deficit/hyperactivity disorder by regulating cAMP and PI3K/AKT pathways - Ren, Xiaodan; Ding, Lele; Jiang, Yonghong (Frontiers in Pharmacology, 2026)
BackgroundAttention-deficit/hyperactivity disorder (ADHD) is a prevalent neurodevelopmental disorder in children. Long Mu Ning Xin Decoction (LMNXD) shows established clinical efficacy against ADHD, yet its mechanistic basis is not fully elucidated.ObjectiveThis study investigates the therapeutic potential of LMNXD for ADHD and explores its underlying mechanisms of action.MethodsThirty spontaneously hypertensive rats (SHRs/NCrl) were randomly divided into five groups: a model (SHR) group, low-, medium-, and high-dose LMNXD (LMNXD-LD, LMNXD-MD, LMNXD-HD)groups, and a methylphenidate hydrochloride (MPH) group. Additionally, six Wistar Kyoto (WKY/NCrl) rats were designated as the control group.Behavioral performance was assessed using the open field test and Morris water maze. The expression levels of glial fibrillary acidic protein (GFAP), dopamine deceptor D1 (DRD1), and brain-derived neurotrophic factor (BDNF) in the rat hippocampus, prefrontal cortex (PFC), and striatum were evaluated by immunofluorescence, immunohistochemistry, and Western blot. Potential targets and mechanisms were explored through transcriptomic sequencing and network pharmacology, with subsequent validation by reverse transcription quantitative polymerase chain reaction (RT-qPCR).ResultsCompared to the SHR group, LMNXD ameliorated hyperactivity, impulsivity, deficits in spatial memory and learning ability in SHR/NCrl rats. It also effectively reduced GFAP expression in the hippocampus while increasing DRD1 expression in the PFC and BDNF levels in the striatum. Network pharmacology predicted that LMNXD might alleviate ADHD by acting on pathways including phosphatidylinositide 3-kinase-Akt (PI3K-Akt), calcium signaling, and cyclic adenosine monophosphate (cAMP) signaling. Consistent with this prediction, transcriptomic analysis of rat hippocampi showed that LMNXD influences the cAMP and PI3K-Akt signaling pathways, as well as serotonergic and cholinergic synapses. RT-qPCR further confirmed that LMNXD likely exerts its therapeutic effect by regulating the mRNA expression of ATPase Plasma Membrane Ca2+ Transporting 4 (ATP2B4), Glutamate Ionotropic Receptor NMDA Type Subunit 3A (GRIN3A), Oxytocin Receptor (OXTR), Collagen Type VI Alpha 2Chain (COL6A2), and Integrin Subunit Alpha 1 (ITGA1) within the cAMP andPI3K-Akt pathways.ConclusionLMNXD may ameliorates hyperactive-impulsive behaviors and improves spatial memory and learning in SHRs/NCrl rats by modulating ATP2B4, GRIN3A, OXTR, COL6A2, and ITGA1 within the cAMP and PI3K-Akt signaling pathways. This intervention also upregulates DRD1 and BDNF expression while downregulating GFAP levels.